Pulmonary embolism diagnosis with D-dimer levels and computed tomography - Rochelle A. Kruger; Jeanetta du Plessis; Henra Muller (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Pulmonary embolism (PE), a common heart and blood vessel disease, causes complications such as haemodynamic instability and cardiovascular mortality. Timely diagnosis and treatment are imperative for managing this potentially life-threatening condition.